Photolysis of 3, 5‐diphenylisoxazole in argon matrices†. (21st September 2016) - Sriyarathne, H. Dushanee M.; Sarkar, Sujan K.; Hatano, Sayaka; Abe, Manabu; Gudmundsdottir, Anna D.; Abe, Manabu; Sheridan, Robert S.
Abstract : Broadband irradiation of 3, 5‐diphenylisoxazole1 in an argon matrix results in formation of azirine3 . Further irradiation of the matrix reduces the amount of azirine3 with concurrent formation of ylide4 . Thus, it is theorized that the conversion of isoxazole1 to azirine3 goes through a triplet vinylnitrene2 that does not intersystem cross to ketenimine6 . Hence, the reactivity of triplet vinylnitrene2 is different from similar vinylnitrene intermediates with α‐methyl substituents that intersystem cross to form corresponding ketenimines. Density functional theory calculations support the notion that the conjugation of the α‐phenyl group to the vinylnitrene moiety in vinylnitrene2 renders it more flexible than vinylnitrenes with α‐methyl substituents, and therefore, vinylnitrene2 intersystem crosses to azirine3, rather than ketenimine6 . Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Broadband irradiation of 3, 5‐diphenylisoxazole 1 in an argon matrix results in formation of azirine 3. Further irradiation of the matrix reduces the amount of azirine 3 with concurrent formation of ylide 4. Thus, it is theorized that the conversion of isoxazole 1 to azirine 3 goes through a triplet vinylnitrene 2 that does not intersystem cross to ketenimine 6.